Aplikasi medan magnet pada saluran bahan bakar sepeda motor - Mara, I Made; Nuarsa, I Made (Jurnal Energi Dan Manufaktur, 2022)
Reducing fuel consumption and improving fuel quality in motorcycle engines are very important in order to make the exhaust gas emission from the engine becomes more environmentally friendly. In this study, a magnetic field is attached to the fuel line so that the fuel is affected by the magnetic field. The magnetic field is obtained from electromagnetic magnets and permanent magnets. Fuel consumption is tested on a motorcycle engine that it uses a carburetor system and on an engine that uses a fuel injection system. The exhaust emissions observed were CO and HC by using exhaust gas analyzer. The results showed that the use of a magnetic field mounted on the fuel line can reduce the fuel consumption of a motorcycle engine, using either a carborator system or a fuel injection system by an average of 18%. The use of magnetic fields also shows a very good effect in reducing exhaust gas emissions from motorcycle engines. The length of the magnet attached to the fuel line, 80mm provides a reduction in exhaust gas emissions of CO by 80% - 90% and HC by 60% - 77%. The percentage reduction in exhause gas emission is better than the other length of magnets.